Acute porphyrias in the Argentinean population: a review. - Parera, V.E. (2003)
The porphyrias are a group of inherited metabolic disorders of heme biosynthesis which result from a partial deficiency in one of its seven specific enzymes, after its first and rate limiting enzyme, delta-aminolevulinic acid synthetase. They can be classified on the basis of their clinical manifestations into cutaneous, acute and mixed disorders. Acute intermittent porphyria (AIP) is the most common type of hepatic acute porphyrias, inherited as an autosomal dominant trait, caused by a defect in the gene which codifies for the heme enzyme porphobilinogen deaminase. Its prevalence in the Argentinean population is about 1:125,000. A partial deficiency in another enzyme, protoporphyrinogen oxidase, produces variegate porphyria (VP), the second acute porphyria most frequent in the Argentinean population (1:600,000). Here, we review all the mutations we have found in 46 AIP and 9 VP unrelated Argentinean patients. To screen for mutations in symptomatic patients, we have proposed a geneticresearch strategy.